The appropriate drying parameters for producing wild carob (Ceratonia siliqua L.) cocoa powder substitute / Aziz Caliskan ... [et al.] - Caliskan, Aziz; Abdullah, Norhidayah; Ishak, Noriza; Engin, Suleyman (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Extant literature has suggested that the demand for chocolate is increasing at a geometric rate while cocoa production is increasing at an arithmetic rate. Hence it is predicted that a point will be reached where the production of cocoa will not accommodate the demand of chocolate production. Therefore, it is rational to seek a suitable alternative that could substitute cocoa. Therefore, this study is focused on utilizing Cypriot Wild Carob Powder (WCP), which is mostly used for animal feeding or thrown away as cocoa powder substitute. The study conducted physiochemical experiments (milling yield, water activity, and colour analysis) on roasting times of 10, 20, and 30 mins at 90, 110, and 130 ° C were tested to determine the optimum drying time and temperature to produce WCP. The results from physical analysis showcased that WCP, which was roasted at 130 °C for 30 mins, showed relatively better water activity (68.9%) and milling yield (85.3%) as compared to the control sample (cocoa powder). However, in terms of water activity and colour analysis, WCP, which was roasted at 130 °C for 30 mins, had the closest value to its control sample (cocoa powder). Hence, this sample was elected as the most suitable for producing WCP as substitute cocoa powder.